Pengaruh Kreativitas dalam Pembelajaran Inkuiri Berbasis Multimedia terhadap Hasil Belajar Siswa pada Pokok Bahasan Ikatan Kimia - Elferida Sormin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2016)
The purposes of the research are : 1. To determine differences in learning outcomes of student with Inquiry_based Learning in Multimedia and Conventional Learning. 2. To determine differences in chemistry learning outcomes of student who have high creativity and low creativity. 3. To determine the interaction between Inquiry based learning in multimedia with the level of creativity in improving student chemistry learning outcomes. The sample in this study conducted in a cluster random sampling of two classes, where the first as a class experiment applied Inquiry based learning in multimedia and the second class of controls implemented Conventional Learning. The instrument used in this study is chemistry learning outcomes test in multiple choice as 30 questions that have been declared valid and reliable. The results were found: there are differences in physical students learning outcomes are taught by Inquiry based learning in multimedia and Conventional Learning. There is a difference in student’s learning outcomes that have high Creativity and Low Creativity. There is no interaction between the Inquiry based Learning in multimedia with student’s level of Creativity in improving learning outcomes chemistry. Keywords: Inquiry based learning in multimedia, level of creativity